Women in Ancient Greek literature: Either Conformist or Rebellious - Fatema, Kaniz (State University of Makassar, 2025)
Greek literature, originating in Greece, has influenced generations across Europe, introducing genres like poetry, tragedy, comedy, and western philosophy. Ancient Greek mythology often depicted women as deceitful and manipulative, reflecting patriarchal society. This study contrasts the portrayal of women in Ancient Greek literature and modern-day literature, focusing on the female protagonists Medea, Clytemnestra, and Jocasta. It examines how these women, through their actions in Medea, Agamemnon, and Oedipus Rex, challenge societal norms and grapple with issues of power, identity, and autonomy. Feminist perspectives highlight how these ancient figures resonate with modern concerns about individuality and gender equality, revealing a long-standing tension between societal conformity and personal agency. This research will delve into the roles of female characters aware of their social position and, thereby, gradually emerging as rebellious and defying figures in their society. This paper elaborately discusses how societal conventions define women as either ideal or evil, based on male standards. By exploring gender expectations across literary eras, the study offers insights into how women navigate these constraints and highlights new avenues for feminist literary discourse. Keywords: Ancient Greek; Conformist; Feminism; Individualism; Male Chauvinism